Revisiting Behaviourism Theory of Learning: an outline with Islamic Education - Khairan Muhammad Arif (TSAQAFAH, 2022)
Research on the correction of the theory of  learning behaviorism perspective of Islamic education aims to reveal and explain the  weaknesses  of the  theory of learning behaviorism introduced and practiced by the figures of the psychological school of behaviorism such as;  Edwart L. Thorndike (1874-1949), Ivan Pavlov (1849-1936) and B. F Skinner (1904-1990), especially related to the  concept of learning, the nature  of  learners and the motivation of learning that many educational practices conventional western, then provides a more precise and comprehensive concept related to learning, the nature of human or learner potential  and learning motivation in the Qur'an and As-Sunnah.   This research method  uses a qualitative method with an analytical description approach that aims to explain and describe the problems studied authentically, literatively and thematically, as well as scientifically analyze  the research object that gives birth to conclusions.  The source of this research is the library (Library Research), by tracing and examining a large part of the main references to the  theory of  behaviorism such as the  work of B.F. Skinner, Science and Human Behavior, works Robert M. Gagne, The Condition of Learning and Theori of Instruction" and others.  The results of this study show that Islamic education found the weaknesses of behaviorist theory me which equated human psychology with animals, equating cognitive and emotional human beings with animals and the view that the motivation of learning is only from outside the human self, so it always requires a stimulus and response in learn. Keywords: Theory, Learning, Behaviorism, Islamic Education